Reproductive and developmental implications of micro- and nanoplastic internalization: Recent advances and perspectives - Zitong Zhang; Jiahua Meng; Jiaqi Tian; Ning Li; Zhen Chen; Xiang Yun; Dandan Song; Fei Li; Shuyin Duan; Lin Zhang (Ecotoxicology and Environmental Safety)
A growing body of evidence exhibits the ubiquitous presence and accumulation of micro- and nanoplastics (MNPs) in the air, drinking water, food, and even inside the body, which has raised concerns about their potential impact on reproductive and developmental health. To comprehensively examine the current state of knowledge regarding MNPs-induced reproductive and developmental toxicity, we conducted this systematic review by focusing on the prevalence of MNPs determined in reproductive tissues and their influences on parental reproduction and offspring development. Our findings demonstrate the detection of MNPs in various human reproductive tissues, including semen, placenta, and ovarian follicular fluid, as well as in reproductive tissues of diverse animal species. We show a potential relationship between MNP exposure and increased prevalence of infertility and adverse pregnancy outcomes based on the fact that MNPs exert detrimental effects on reproductive parameters, including sperm quality, ovarian function, and steroidogenesis. In male reproductive systems, MNPs disrupt testicular tissue structure, impair reproductive endocrinology, and reduce sperm quality. In females, MNPs affect ovarian tissue structure and function, interfere with hormone secretion, and impact the endometrium and embryo implantation. Additionally, MNPs cause developmental toxicity in animal models, affecting embryonic development and offspring health, and produce transgenerational effects. Notably, in-depth literature study suggests a crucial role for oxidative stress, inflammation, and epigenetic modification in MNPs-induced toxicity. In conclusion, we integrated systematic knowledge on MNPs-induced reproductive and developmental toxicity, and the systematic finding underscores future study to fully elucidate the risks posed by MNPs to reproductive and developmental health and to inform policy decisions and public health interventions aimed at mitigating their harmful effects.